Her-2 neu negative lipid rich breast carcinoma in an immunocompromised patient - Deepika Sirohi, M.D; Kent Swimley; Amanda L. Profit, M.D; Nicole D. Riddle, M.D (Elsevier, 2015)
Lipid-rich breast carcinoma (LRBC) is rare cancer considered to be a variant of invasive ductal breast carcinoma. It is characterized by an aggressive behavior and poor prognosis and requires prompt recognition and close follow-up. The tumor derives its name from the intracytoplasmic neutral lipid that gives it a vacuolated appearance and is included in the current WHO classification. We report here a case of Her-2 neu negative lipid-rich carcinoma of the breast occurring in a HIV positive woman.